2017
DOI: 10.1021/acs.biomac.6b01756
|View full text |Cite
|
Sign up to set email alerts
|

Annexin V-Conjugated Mixed Micelles as a Potential Drug Delivery System for Targeted Thrombolysis

Abstract: To alleviate the hemorrhagic side effect of thrombolysis therapy, a thrombus targeted drug delivery system based on the specific affinity of Annexin V to phosphatidylserine exposed on the membrane surface of activated platelet was developed. The amphiphilic and biodegradable biomaterial, polycaprolactone-block-poly(2-(dimethylamino)ethyl methacrylate)-block-poly(2-hydroxyethyl methacrylate) (PCL-b-PDMAEMA-b-PHEMA (PCDH)) triblock polymer, was synthesized via ring opening polymerization (ROP) and atom transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…[ 71 ] Annexin V, a protein that specifically binds to PS, has been studied to target nanoparticles to thrombus sites for imaging applications and targeted thrombolysis. [ 72,73 ]…”
Section: Thrombosis Targetingmentioning
confidence: 99%
“…[ 71 ] Annexin V, a protein that specifically binds to PS, has been studied to target nanoparticles to thrombus sites for imaging applications and targeted thrombolysis. [ 72,73 ]…”
Section: Thrombosis Targetingmentioning
confidence: 99%
“…There are many other polymer-based thrombolytic agent-delivery systems [ 43 , 65 , 66 ]. Colasuonno et al prepared a kind of erythrocyte-inspired discoidal nano-construct using PLGA and PEG, and the unique structure could prevent drug accumulation within the brain and reduce cerebral hemorrhages.…”
Section: Nanostructure-based Drug Deliverymentioning
confidence: 99%
“…Recently, platelet-targeting peptides- or small molecules-modified micelles/liposomes, shown in Table 3, were reported to deliver thrombolytic drugs to prevent platelet aggregation (Gupta et al, 2005; Yan et al, 2005; Modery et al, 2011). Pan et al developed a Amnexin V-conjugated micelle that was synthesized with biodegradable polymer and loaded with lumbrokinase for phosphatidylserine thrombolysis (Pan et al, 2017). In vitro experiments have shown that such micelles are much more efficient in thrombolysis than the control group.…”
Section: Nanomedicines For Hemostasis-responsive Componentmentioning
confidence: 99%